If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 4 = 13 + 6x Reorder the terms: 4 + 8x = 13 + 6x Solving 4 + 8x = 13 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 4 + 8x + -6x = 13 + 6x + -6x Combine like terms: 8x + -6x = 2x 4 + 2x = 13 + 6x + -6x Combine like terms: 6x + -6x = 0 4 + 2x = 13 + 0 4 + 2x = 13 Add '-4' to each side of the equation. 4 + -4 + 2x = 13 + -4 Combine like terms: 4 + -4 = 0 0 + 2x = 13 + -4 2x = 13 + -4 Combine like terms: 13 + -4 = 9 2x = 9 Divide each side by '2'. x = 4.5 Simplifying x = 4.5
| In(x+5)+(x-5)=(4x+7) | | 8/9-1/8 | | f(7)=4/49= | | v-5=12 | | 2x-10=6x^1 | | 12x^2-43x+35= | | 3y-26=55 | | 3-19=2z+6z | | 2x-10=6x^2 | | 5x=4x-80 | | -7x-3+1=3.8 | | -107-8x=-17x+19 | | 4(a+2)=2a(a+6) | | 6x=y-8 | | 3x-4=2z+7 | | (2-3y)(5y+1)= | | X+4*3=51 | | 10-3n=55 | | -9(x+3)+5(3x-7)=5(x-6)+9 | | 2y=-70+64 | | b=1/2ps | | -3(k+1)-k-8=4(k+4)+5 | | 5p-8=10p-28 | | 14x+4=9x-11 | | 3x-7+9-2=x+2 | | 4b-3a=8b | | Y^2-225= | | 5x+22=7x+32 | | 12x-24=4x+8 | | (x*.0625)+(x*.2)+x=30 | | 15-4y=51 | | 9(x+4)-7=37-2x-8+11x |